Vena Cava Filter Misplacement: A Killer Traveler - Garcia, Leonardo Rufino [UNESP]; Garzesi, André Monti [UNESP]; Martins, Antonio Sérgio [UNESP]; Sobreira, Marcone Lima [UNESP]; Brito, Flavio de Souza [UNESP]; Felicio, Marcello Laneza [UNESP] (Sociedade Brasileira de Cirurgia Cardiovascular, 2022)
Inferior vena cava filter embolization is not uncommon and can reach 11.8%. However, device migration to the heart is not frequent and occurs in cases after inferior vena cava filter fracture. We present the case of a young woman who was submitted to a routine inferior vena cava filter placement three days before and presented with hemodynamic instability. Since the device was not retrievable, the surgical team opted for an open cardiac surgery under cardiopulmonary bypass to remove the inferior vena cava filter and avoid other further complications.
Keywords: Cardiopulmonary Bypass; Thoracic Surgery; Equipment and Supplies; Hemodynamics; Vena Cava Filters